2018
DOI: 10.1002/da.22819
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold PTSD and PTSD in a prospective‐longitudinal cohort of military personnel: Potential targets for preventive interventions

Abstract: Subthreshold PTSD accounted for a substantial proportion of this population's future PTSD burden. Population-based preventive interventions, compared to an approach focused exclusively on cases of diagnosable PTSD, is likely to affect the greatest reduction in this population's future PTSD burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 37 publications
1
27
1
Order By: Relevance
“…To this date, only two longitudinal studies have examined the long‐term course of subthreshold PTSD. Cukor et al (2010) found that 14.1% of subthreshold PTSD among rescue workers who worked at the World Trade Center following 9/11 progressed to PTSD, and Fink et al (2018) reported that 15.9–17.3% of subthreshold PTSD in a military cohort advanced to probable PTSD per year. Goodwin et al (2012) found that delayed‐onset PTSD, defined as the onset of PTSD at least 6 months after a traumatic event represented nearly half of all PTSD cases assessed within their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this date, only two longitudinal studies have examined the long‐term course of subthreshold PTSD. Cukor et al (2010) found that 14.1% of subthreshold PTSD among rescue workers who worked at the World Trade Center following 9/11 progressed to PTSD, and Fink et al (2018) reported that 15.9–17.3% of subthreshold PTSD in a military cohort advanced to probable PTSD per year. Goodwin et al (2012) found that delayed‐onset PTSD, defined as the onset of PTSD at least 6 months after a traumatic event represented nearly half of all PTSD cases assessed within their study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has found that subthreshold PTSD is as prevalent and sometimes even more prevalent than full‐threshold PTSD in community samples (Mitchell, Mazzeo, Schlesinger, Brewewrton, & Smith, 2012, Pietrzak, Goldstein, Southwick, & Grant, 2011a). Studies on military personnel and the police, who are inevitably exposed to trauma due to the nature of their occupation, found an even higher rate of subthreshold PTSD than reported in community samples (Fink et al, 2018; Pietrzak et al, 2012). In 1988, the first major study on subthreshold PTSD by Kulka et al (1988) reported that 11% of male Vietnam veterans and 7.8% of female veterans currently suffered from subthreshold PTSD.…”
Section: Introductionmentioning
confidence: 93%
“…Soldiers who have served in current‐era conflicts have PTSD estimates of 13.5% among all veterans and 15.8% among OEF/OIF veterans . Further, it is estimated that approximately 25% of veterans and 12% of current Guard soldiers experience subclinical PTSD symptomatology . These symptoms have also been shown to be associated with poor physical and mental health …”
Section: Introductionmentioning
confidence: 99%
“…7 Brancu et al 11 performed a meta-analysis of the literature on sub-syndromal PTSD in civilian and military populations, noting five possible definitions for the condition and an average prevalence rate of 14.7%. Furthermore, a large prospective study of US National Guard personnel 12 found 12% screened positive for sub-syndromal PTSD and only 5% with probable PTSD. Finally, Van Hooff et al 13 suggested that as many as 38% of a large cohort who had transitioned from the Australian Defence Force and 20.2% of current serving personnel surveyed in 2015 could be considered to have sub-threshold PTSD based upon scores in the moderate to very high bands of the PCL-C that was performed anonymously and thus free of the risk of minimisation of symptoms, a problem seen in identified military screening.…”
Section: Prevalence Of Sub-syndromal Ptsdmentioning
confidence: 99%
“…Identifying and effectively treating those with sub-syndromal PTSD should be a priority because of its association with delayed-onset PTSD and other conditions. Fink et al 12 suggested that effective treatment of a cohort of US National Guard personnel with sub-syndromal PTSD could theoretically reduce the population burden of future diagnosable PTSD by over a third. However, currently there are no clear guidelines as only a few studies have assessed treatment for sub-syndromal PTSD in veterans.…”
Section: Treatment and Sub-syndromal Ptsdmentioning
confidence: 99%